Sustainable Food Security: An Emerging Research and Policy Agenda - Sonnino, Roberta; Faus, Ana Moragues; Maggio, Albino (The International Journal of Sociology of Agriculture and Food, 2014)
As a response to emerging calls for the adoption of a systemic approach to food security, in this article we identify and discuss inextricably linked barriers to ‘sustainable food security’. Based on an extensive analysis of recent academic and policy literatures on the economic, social and ecological effects of global environmental change at different stages of the food system, we highlight a series of cross-cutting issues and areas of disconnection between food production and consumption that call for a renovated focus on the different nodal points of the food system. As we suggest, a sustainable food security framework should move away from the conventional focus on individual components of the food system (e.g., supply and demand) and address more holistically the complex relationships between its different stages and actors.